Experimental test methodology to evaluate sound propagation paths between interior spaces of buildings - Gervásio, Nuno (2018)
When is detected in situ the existence of poor sound insulation, typically the non-compliance with the acoustic requirements of buildings, between two spaces – source and receiver - and if we want to solve the problem, it is necessary to know which sound paths most contribute to the difference of sound levels between these spaces. However, the classical sound insulation measurement does not make this distinction, it only provides the difference in sound levels. In order to overcome this difficulty, a new test methodology is proposed to estimate the sound propagation paths between building rooms, generated by sound sources located in the interior. The proposed methodology is based on the use of vibration measurements of structural elements (slabs) and non-structural elements (parti-tion walls) to estimate the sound field in the receiver space, together with sound measure-ments to estimate the sound field in the source space. With this alternative methodology to determine the sound insulation of a space, it is intended to obtain more rigorous results with respect to: i) determination of the contribution of each of the structural paths, in a certain sound isolation, in order to define the sound paths in which an acoustic rehabilita-tion intervention is most effective; ii) determining the possible existence of airborne paths that contribute to the reduction of sound insulation. In order to validate the proposed methodology, in situ sound insulation measurements were carried out, according to the applicable standards of ISO 16283 series, and vibration measurements of the separator el-ements (floor, ceiling, side walls) of interior spaces in existing buildings.